Reframing EFL syllabus design for the 21st century: exploring teacher readiness in pre-service education - Sucipto, Sucipto; Muh Saeful Effendi; Arum Priadi; Olivi Sabilla Sadani (Journal of English and Education (JEE), 2026)
This study explores how pre-service English teachers develop readiness to integrate 21st-century competencies and sustainability principles into English as a Foreign Language syllabus design. Grounded in experiential learning theory and the framework of global competence, the study aims to examine the level of readiness, the relationship between familiarity and confidence, and the factors shaping the transition from conceptual understanding to pedagogical practice. This study employed an explanatory sequential mixed-method design, combining quantitative data from a structured questionnaire with qualitative insights from reflective narratives. The findings reveal that participants demonstrate strong conceptual understanding but uneven confidence and limited practical application. The results indicate that familiarity with key concepts does not necessarily lead to effective implementation without reflective experience and contextual support. The study concludes that teacher readiness is a dynamic process shaped by the interaction between knowledge, belief, and practice rather than a fixed competency. These findings imply the importance of integrating mentorship, reflective inquiry, and contextualized learning experiences into teacher education programs to support the meaningful application of global and sustainability-oriented competencies in language teaching.